ANALISA KEBERLANJUTAN SISTEM PENYEDIAAN AIR MINUM PERDESAAN BERBASIS MASYARAKAT (STUDI KASUS: PROGRAM PAMSIMAS DESA PONGGANG DAN DESA TALAGASARI, KABUPATEN SUBANG, PROVINSI JAWA BARAT: ANALISA KEBERLANJUTAN SISTEM PENYEDIAAN AIR MINUM PERDESAAN BERBASIS MASYARAKAT (STUDI KASUS: PROGRAM PAMSIMAS DESA PONGGANG DAN DESA TALAGASARI, KABUPATEN SUBANG, PROVINSI JAWA BARAT - reza eka putra (Jurnal Teknik Lingkungan, 2021)
The fulfillment of drinking water access in rural areas has only reached 56.09% compared to its target at 65.81% in 2015. Sustainable Development Goals (SDGs) target in 2019, that is universal access for clean water sector, especially those in rural areas in Indonesia, is accompanied by the involvement of local residents (community based) within the development of clean water provision system for rural areas, as well as using the demand responsive approach. PAMSIMAS program has its own challenge in guaranteeing the sustainability, considering the limited program management capacity of local residents. The study aims to know rural water supply performance condition, and evaluate the components of sustainable community based Rural Water Supply (RWS) system, which consist of the following variables: technical, environmental, finance, social, and institutional using descriptive analysis and Simple Additive Weighting Method (SAW). This valuation was performed quantitatively through use expert questionnaires instruments and questionnaires for local who have reaped benefit from the PAMSIMAS. The descriptive analysis result, for the sustainability percentage performance of PAMSIMAS in the village of Ponggang, were technical sustainability (95.94%), environmental sustainability (98.54%), financial sustainability (90.63%), social sustainability (83.13%), and institutional sustainability (92.19%). Meanwhile for PAMSIMAS in the village of Talagasari, the results were technical sustainability (49.8%), environmental sustainability (86.72%), finance sustainability (69.27%), social sustainability (54.17%), and institutional sustainability (36.33%). Sustainability index RWS based on Simple Additive Weighting analysis for PAMSIMAS in the village of Ponggang had a score of 1 and PAMSIMAS in the village of Talagasari obtained a score of 0.568. Thus PAMSIMAS in Ponggang was valued to be more sustainable.